Quality of Service Gateway Load Balancing Protocol Message Digest Algorithm 5 Authentication untuk Peningkatan Kualitas Jaringan - Firmansyah, Firmansyah; Dewi, Sari; Purnama, Rachmat Adi (LPPM STMIK ANTAR BANGSA, 2019)
Abstract—Gateway Load Balancing Protocol (GLBP) Message-Digest algorithm 5 (MD5) is a Cisco's proprietary protocol. GLBP used to enhance the Quality of Service(QoS) on a network. It applies the IP Address Gateway Virtual that redundancy on the local network. GLBP run all used routers in time because of load balancing itself, there is no router used as a standby/backup only. Using the GLBP protocol, all network loads are shared equally to all connected routers. The way the GLBP network works is different from how the HSRP and VRRP networks work, which will run the standby/backup router if the active / master router experiences a problem (failover). The average time needed to redundancy the master to router backup router is 7.6 ms. While the average time needed to change from standby router redundancy to master router redundancy or the master router reused is 33.4 Ms. The average packet loss obtained when the redundancy of the active router change to standby router is 1.7 packet, and The average packet loss obtained when the redundancy of the active router change to standby router is 1.7 packet and 0.5 packets in opposite ways. Intisari— Gateway Load Balancing Protocol (GLBP) Message Digest algorith 5 (MD5) merupakan sebuah protokol Cisco proprietary. GLBP dibentuk untuk meningkatkan Quality of Service (QoS) terhadap jaringan komputer dikarenakan menggunakan IP Address Gateway Virtual yang bersifat redundancy pada jaringan lokal. GLBP menjalankan semua router yang digunakan secara bersamaan dikarenakan sifatnya Load Balancing itu sendiri, sehingga tidak ada router yang bersifat hanya standby/backup saja. Dengan menggunakan protokol GLBP, semua beban jaringan dibagi sama rata kepada semua router yang terhubung. Cara kerja jaringan GLBP berbeda dengan cara kerja jaringan HSRP dan VRRP yang akan menjalankan router standby/backup jika router active/master mengalami sebuah permasalahan (fail over). Adapun waktu rata-rata yang dibutuhkan untuk melakukan redundancy router master to router backup adalah 7,6 Ms. Sedangkan waktu rata-rata yang dibutuhkan untuk melakukan redundancy router standby to router master ataupun ketika router master telah dapat digunakan kembali adalah 33,4 Ms. Sedangkan hasil rata-rata packet loss yang didapat saat redundancy router active to router standby adalah 1,7 packet loss dan packet loss yang didapat saat terjadi redundancy router standby to router master sebesar 0,5 packet. Kata Kunci — Gateway Load Balancing Protocol, Quality of Service, Redundancy, Packet Loss